Produktivitas Perempuan Pekerja Penyintas TB di Indonesia: Peran Kesejahteraan Psikologis - Anindita, Rina; Novianna, Yoan (Jurnal Kesehatan Komunitas, 2025)
Indonesia ranks second in the world for the highest number of Tuberculosis (TB) cases, with approximately 30% of patients being women of productive age. The lengthy TB treatment process often requires extended leave from work, which can negatively impact mental health due to social stigma and concerns about transmission. This quantitative study aims to analyze the factors influencing the intention of female TB survivors to return to work, by integrating the Theory of Planned Behavior and psychological well-being. The survey involved 238 respondents from the PETA-TB community in Jakarta, Tangerang, and Bandung. Data were analyzed using SEM-PLS with R-Studio. The results show that subjective norms positively affect both psychological well-being and return-to-work intention, while perceived health influences psychological well-being but not directly the intention to return to work. Psychological well-being is confirmed as a key mediating factor between social support and the intention to return to work.